Towards Long-Term Photostability of Solid-State Dye Sensitized Solar Cells - Pathak, S; Abate, A; Leijtens, T; Hollman, D; Teuscher, J; Pazos, L; Docampo, P; Steiner, U; Snaith, H (2014)
The solid-state dye-sensitized solar cell (DSSC) was introduced to overcome inherent manufacturing and instability issues of the electrolyte-based DSSC and progress has been made to deliver high photovoltaic efficiencies at low cost. However, despite 15 years research and development, there still remains no clear demonstration of long-term stability. Here, solid-state DSSCs are subjected to the severe aging conditions of continuous illumination at an elevated temperature. A fast deterioration in performance is observed for devices encapsulated in the absence of oxygen. The photovoltaic performance recovers when re-exposed to air. This reversible behavior is attributed to three related processes: i) the creation of light and oxygen sensitive electronic shunting paths between TiO and the top metal electrode, ii) increased recombination at the TiO/organic interface, and iii) the creation of deep electron traps that reduce the photocurrent. The device deterioration is remedied by the formation of an insulating alumino-silicate shell around the TiO nanocrystals, which reduces interfacial recombination, and the introduction of an insulating mesoporous SiO buffer layer between the top electrode and TiO, which acts as a permanent insulating barrier between the TiO and the metal electrode, preventing shunting. © 2014 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.